Regulation through reference prices - Alfredo Salgado-Torres (Estudios Económicos, 2024)
We analyze the role of reference prices on competition and welfare in a circular city model where paying prices above a reference negatively affects consumers' utility. Agents interact in a three-stage game. First, a policymaker chooses a reference price; second, firms make their entry decision; finally, firms compete in prices while consumers make their consumption decisions. We find that the market price and the optimal reference price always coincide in equilibrium, reducing consumer prices and implying a net welfare gain.